PHARMACY, PHARMACIST, AND SOCIAL PHARMACY - Sudjaswadi, Riswaka (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2001)
In order to express more clearly about the role of pharmacist in the health care, a general review of the sources of the pharmacy (pharmacist) has been carried out. Considering the facts and several survey results, Pharmacy/Pharmacist is a typical profession capabler to develop wider in a health care system and that provides more beneficial for community along with the advancement of Social Pharmacy.Key words: Profession, Professional, changing context of Pharmacy, Professionalization.